1994
DOI: 10.1021/bp00025a005
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling in Individual BC3H1 Cells: Speed of Calcium Mobilization and Heterogeneity

Abstract: Receptor/ligand binding on a cell surface may activate the calcium signal transduction cascade, resulting in the release of calcium from intracellular stores into the cytosol. Changes in intracellular free calcium, [Ca2+]i, following ligand stimulation have been linked to a variety of cell responses, from muscle contraction to hormone secretion. We have monitored changes in [Ca2+]i in single smooth muscle‐like BC3H1 cells following stimulation by the vasoconstrictor phenylephrine, using the fluorescent calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 57 publications
4
21
0
Order By: Relevance
“…The IP 3 production and decay rate constants, k 1 = 5.46 x 10-3 µM s-1 and k 2 = 0.2 s-1 , are chosen to maintain a comparable timescale for IPa production, and a comparable steady state con\:!entration of IP 3 , at physiological levels of ATP. These values are similar to those cited by Mahama and Linderman (1994).…”
Section: Barakat (2001)supporting
confidence: 91%
See 2 more Smart Citations
“…The IP 3 production and decay rate constants, k 1 = 5.46 x 10-3 µM s-1 and k 2 = 0.2 s-1 , are chosen to maintain a comparable timescale for IPa production, and a comparable steady state con\:!entration of IP 3 , at physiological levels of ATP. These values are similar to those cited by Mahama and Linderman (1994).…”
Section: Barakat (2001)supporting
confidence: 91%
“…This phenomenon is termed Ca 2 +-induced Ca 2 + release (CICR) (Wood and Gillespie, 1998). The increased concentration of cytosolic Ca 2 + can also act cooperatively to increase IP 3 production, via increased phospholipase C activity (Mahama and Linderman, 1994;Meyer and Stryer, 1988). Furthermore, release of Ca 2 + from stores appears to stimulates influx of Ca 2 + across the plasma membrane, a process termed capacitative calcium entry (CCE) (Putney et al, 2001).…”
Section: Model For Endothelial Calcium Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, our simulations here do not incorporate cell-tocell variation in parameter values. We have previously shown that such variation, particularly when threshold-like behavior is present in later steps in the activation pathway, leads to a flattening (smaller Hill coefficient) of the dose-response curve (Mahama and Linderman, 1994). In addition, large Hill coefficients in our simulations may also be due to particular assumptions about molecular movement and reaction (e.g., movement is constrained to a lattice and the entire circumference of a molecule is considered to be equally reactive).…”
Section: Antagonist Dissociation Rate Constant Can Modulate G-proteinmentioning
confidence: 81%
“…This allows, even when binding has equilibrated, for the continual movement of ligands among surface receptors. In previous theoretical and experimental studies, when comparing cases of equal occupancy of receptors by agonist, increased movement of agonist (shorter half-life of the receptor-agonist complex) resulted in increased G-protein activation, as receptors newly occupied by agonist have access to Gproteins close by (Mahama and Linderman, 1994;Shea et al, 1997;Stickle and Barber, 1993). Such movement has also been predicted to partially decouple G-protein activation from receptor phosphorylation .…”
Section: Introductionmentioning
confidence: 98%